Biomechanical analysis of starting preference for expert swimmers - Vantorre, J.; Seifert, L.; Vilas-Boas, J. P.; Fernandes, R.; Bideau, B.; Nicolas, G.; Chollet, D. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to compare kinetics, body angles and angular momenta during the swimming start for preferred and non-preferred technique of expert grab starters. Results showed that in preferred technique, starts were executed with less global angular momentum around the transverse axis. By searching further, less loss of angular momentum in the other dimensions was found for grab start as preferred technique, inducing a less efficiency in non-preferred technique (twisting effect in track start as non-preferred technique). Body angles showed that legs in non-preferred technique permit to increase quantity of body rotation during aerial phase. Finally, subject effect was found for arms movements (confirming that expert swimmers can organize themselves differently to achieve to an optimal performance.